PERLINDUNGAN HUKUM BAGI KONSUMEN TERKAIT KLAIM BERLEBIHAN (OVERCLAIM) PELAKU USAHA SKINCARE PADA MEDIA SOSIAL TIKTOK - NIM. A1011211233, TRI WAHDANIA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Overclaiming in skincare product promotions on TikTok has become a detrimental phenomenon for consumers. Business actors frequently make exaggerated claims without valid scientific basis, thereby misleading consumers and potentially endangering skin health, as well as causing material and immaterial losses such as financial loss, wasted time, skin damage, and emotional disappointment. This research aims to investigate the legal protections available for consumers and the forms of business actors